Key indicators for appraising adolescent sexual and reproductive health in South Asia: international expert consensus exercise using the Delphi technique - Furqan Ahmed; Ghufran Ahmad; Tilman Brand; Hajo Zeeb (Taylor & Francis Group, 2020)
Background There is a need for an accurate assessment of the patterns and determinants of sexual and reproductive health in South Asia owing to high fertility rates and high incidence of unplanned pregnancy among adolescents. Health indicator sets, with a wide range of health dimensions, also support in formulating evidence-based policies. For attaining this, indicators should be developed and prioritized based on consensus and relevance. Objective This study aimed to develop a comprehensive list of adolescent sexual and reproductive health (ASRH) key indicators for South Asia through systematic participatory expert consultation exercise using the Delphi technique. Methods Experts were invited to two rounds of an indicator rating exercise and a third round to discuss the results in a broader regional perspective. A list of nine indicator categories, including 41 adolescent health indicators, was rated by the expert panel. Prioritization was based on mean Likert scores while consensus was established using Kendall's W. Results 24, 16 and six experts participated in the first, second and third round, respectively. Out of the nine indicator categories, demographics, reproductive health, violence, and nutrition were ranked high in relevance by the expert panel. Experts had a strong consensus on the relevance of parental control and connection, and behavioral indicators while there was moderate consensus on the relevance of nutrition, infectious disease, and mortality indicators. Conclusion As far as we know, this is the first study that employs the Delphi technique for prioritizing ASRH indicators for South Asia. Engaging a diverse group of experts, using an online platform, we developed a comprehensive list of key indicators for appraising ASRH relevant to South Asia based on expert panel consensus and recommendations. Our results also highlight that there is a need for developing a region-specific prioritized list of indicators which might assist in identifying regional health needs.